SVARTLAMON: A MODEL OF URBAN-SCALE SUSTAINABILITY AND COMMUNITY INNOVATION IN NORWAY - Prabowo, Bintang Noor (MODUL, 2024)
The Svartlamon district of Trondheim, Norway, as a pioneering example of community-driven sustainability within an urban experimental framework, is investigated in this paper. Municipal authorities have assigned Svartlamon as a special area for testing innovative sustainable urban living solutions, thus making it a unique case study in integrating social, environmental, and financial sustainability at the local level. By means of comprehensive case studies, this study investigates several projects carried out in Svartlamon, including green building projects such as the Eksperimentboliger, waste management systems, participatory community governance models, urban agriculture, sustainable transportation programs, community-operated renewable energy installations, and educational and cultural events meant to raise environmental awareness and community cohesion. The results of Svartlamon experiment provided insight into how well community-driven initiatives might generate significant environmental benefits and improve social ties in urban environments. These projects not only help to lower the environmental impact by achieving better resource efficiency and waste reduction but also strengthen the resilience and sustainability of the urban community by encouraging active participation and involvement among the citizens. This paper addresses the scalability and replicability of Svartlamon's practices, thereby providing insightful guidance for urban designers and policymakers engaged in similar projects intended to include sustainability into urban development. The study emphasizes the possibility of localized, community-based initiatives in changing urban environments and implies that sustainable urban development in the twenty-first century depends on such methods.